Method for producing stress-induced luminescent material

JP7640132B2Active Publication Date: 2025-03-05NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023503970
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-05
Filing Date
2022-03-04
Publication Date
2025-03-05
Estimated Expiration
2042-03-04

AI Technical Summary

Benefits of technology

【0026】 また、本発明に係る応力発光材料の製造方法によれば、亜鉛化合物と、発光中心イオンを供給する発光中心供給化合物と、共添加イオンを供給する所定の共添加イオン供給化合物と、を混合し、同混合物(ただし、加熱により溶融して反応系を酸化雰囲気から隔離する固体保護剤を含むものを除く。)を酸化雰囲気下にて焼成するZnOを母体材料とした応力発光材料の製造方法であって、前記発光中心イオンは、Ndのイオン又はNdのイオン及びCr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, Ybから選ばれるいずれか1つの元素のイオンであり、前記共添加イオンは、Li, Na, K, Rb, Csから選ばれるいずれか1つの元素のイオン又はLi及びBaのイオンであり、前記応力発光材料は、一般式ZnO:ExMy(ただし、Eは前記共添加イオンであり、Mは前記発光中心イオン。)で表される組成を有し、x=0.0001~0.7であって、y=0.001~0.2であることとしたため、ZnOを母体材料とする応力発光材料の製造方法を提供することができる。特に、所定の共添加イオン供給化合物を銀イオン供給化合物、アルミニウムイオン供給化合物又はアルカリ金属化合物とすれば、ZnOを母体材料とする応力発光材料をより堅実に製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640132000001
    Figure 0007640132000001
  • Figure 0007640132000002
    Figure 0007640132000002
  • Figure 0007640132000003
    Figure 0007640132000003
Patent Text Reader

Abstract

Provided is a stress-stimulated luminescent material that uses ZnO as a base material. The material was obtained by forming a solid solution of a luminescence center ion and a predetermined co-added ion in ZnO. Also, the material has a composition represented by the general formula ZnO:ExMy (where, E is the predetermined co-added ion and M is a luminescence center ion which is at least one metal ion selected from transition metal ions and rare earth ions.) and characteristics such as the fact that x=0.0001-0.7 and y=0.001-0.2, and the predetermined co-added ion is a silver ion, an aluminum ion, or an alkali metal ion, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a stress-stimulated luminescent material and a method for producing the stress-stimulated luminescent material. [Background technology]

[0002] The present inventors have been the first in the world to invent a mechanoluminescent material and have developed its industrial application.

[0003] Mechanoluminescent materials are materials that emit luminescence correlated with the energy of an external mechanical stimulus, and are expected to be used in a wide variety of applications, including sensors, non-destructive testing, visualization of stress distribution, stress sensing, and detection of abnormalities and dangers in structures.

[0004] Therefore, stress-stimulated luminescent materials capable of emitting light in response to stress at various wavelengths ranging from ultraviolet to near-infrared wavelengths have been developed.

[0005] In particular, the inventors have been conducting intensive research in this technical field day and night and have proposed a wide variety of stress-stimulated luminescent materials, such as an SAO-based stress-stimulated luminescent material that emits green light with high luminance (see, for example, Patent Document 1 and Patent Document 2), a LiNbO3-based stress-stimulated luminescent material that is sensitive to even minute stresses and emits light in the visible light range (see, for example, Patent Document 3), and an SSN-based stress-stimulated luminescent material that emits stress-stimulated light in the near-infrared range (see, for example, Patent Document 4). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2001-049251 A [Patent Document 2] International Publication No. 2005 / 097946 [Patent Document 3] International Publication No. 2018 / 070072 [Patent Document 4] JP 2015-086327 A Summary of the Invention [Problem to be solved by the invention]

[0007] ZnO (zinc oxide) has a wide range of applications, from pigments and paints to catalyst materials and pharmaceuticals, and is used in a variety of fields as a relatively common material in modern times.

[0008] In addition, ZnO has been the subject of extensive research in a variety of fields for a long time, and in terms of its physical properties, for example, it is known that it can have a variety of particle shapes and optical properties depending on the material design and synthesis process.

[0009] However, no mechanoluminescent materials using ZnO as a host material have been reported to date, and they were thought to be impossible to realize.

[0010] The present invention has been made in view of the above circumstances, and provides a stress-stimulated luminescent material using ZnO as a host material.

[0011] The present invention also provides a method for producing a stress-stimulated luminescent material using ZnO as a host material, and a method for producing a stress-stimulated luminescent material from ZnO. [Means for solving the problem]

[0015] In order to solve the above conventional problems, In the method for producing a stress-stimulated luminescent material according to the present invention, ( 1 ) a zinc compound; Luminescent center supply that supplies luminescent center ions A compound, Supplying co-doped ions Mix with a specified co-additive ion donor compound. The mixture (excluding those containing a solid protective agent that melts when heated to isolate the reaction system from an oxidizing atmosphere) Firing in an oxidizing atmosphere A method for producing a stress-stimulated luminescent material using ZnO as a base material, the luminescent center ion is an ion of Nd or an ion of Nd and any one element selected from Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb, the co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba, and the stress-stimulated luminescent material is represented by a general formula ZnO:E x M y (wherein E is the co-doped ion, and M is the luminescent center ion), and x=0.0001 to 0.7, and y=0.001 to 0.2. It was decided.

[0017] In addition, in the method for producing a stress-stimulated luminescent material according to the present invention, ( 2) making the aqueous solution containing zinc ions in which a luminescent center ion and a predetermined co-doped ion are present basic, or reacting the aqueous solution with a sulfide to coprecipitate the co-doped ion and the luminescent center ion with zinc hydroxide or zinc sulfide, and (However, this does not include solid protective agents that melt when heated to isolate the reaction system from an oxidizing atmosphere.) The mixture is fired in an oxidizing atmosphere. A method for producing a stress-stimulated luminescent material using ZnO as a base material, the luminescent center ion is an ion of Nd or an ion of Nd and any one element selected from Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb, the co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba, and the stress-stimulated luminescent material is represented by a general formula ZnO:E x M y (wherein E is the co-doped ion, and M is the luminescent center ion), and x=0.0001 to 0.7, and y=0.001 to 0.2. It was decided. Effect of the Invention

[0026] In addition, according to the method for producing a stress-stimulated luminescent material of the present invention, a zinc compound and Luminescent center supply that supplies luminescent center ions A compound, Supplying co-doped ions Mix with a specified co-additive ion donor compound. The mixture (excluding those containing a solid protective agent that melts when heated to isolate the reaction system from an oxidizing atmosphere) Firing in an oxidizing atmosphere A method for producing a stress-stimulated luminescent material using ZnO as a base material, the luminescent center ion is an ion of Nd or an ion of Nd and any one element selected from Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb, the co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba, and the stress-stimulated luminescent material is represented by a general formula ZnO:E x M y (wherein E is the co-doped ion, and M is the luminescent center ion), and x=0.0001 to 0.7, and y=0.001 to 0.2. Therefore, it is possible to provide a method for producing a stress-stimulated luminescent material using ZnO as a base material. In particular, if the predetermined co-doped ion supplying compound is a silver ion supplying compound, an aluminum ion supplying compound, or an alkali metal compound, it is possible to more reliably produce a stress-stimulated luminescent material using ZnO as a base material.

[0027] In addition, according to the method for producing a stress-stimulated luminescent material of the present invention, the aqueous solution containing zinc ions in which a luminescent center ion and a predetermined co-doped ion are present is made alkaline or a sulfide is reacted with the aqueous solution to coprecipitate the co-doped ion and the luminescent center ion with zinc hydroxide or zinc sulfide, and the coprecipitate is (However, this does not include solid protective agents that melt when heated to isolate the reaction system from an oxidizing atmosphere.) The mixture is fired in an oxidizing atmosphere. A method for producing a stress-stimulated luminescent material using ZnO as a base material, the luminescent center ion is an ion of Nd or an ion of Nd and any one element selected from Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb, the co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba, and the stress-stimulated luminescent material is represented by a general formula ZnO:E x M y (wherein E is the co-doped ion, and M is the luminescent center ion), and x=0.0001 to 0.7, and y=0.001 to 0.2. Therefore, it is possible to provide a method for producing a stress-stimulated luminescent material using ZnO as a host material. In particular, if the predetermined co-doped ions are silver ions, aluminum ions or alkali metal ions, it is possible to more reliably produce a stress-stimulated luminescent material using ZnO as a host material. [Brief description of the drawings]

[0030] [Figure 1] FIG. 2 is an explanatory diagram showing the crystal structure of ZnO. [Diagram 2] FIG. 2 is an explanatory diagram showing an XRD diffraction pattern of ZnO:Nd0.006,Li0.006. [Diagram 3] FIG. 2 is an explanatory diagram showing an SEM image of ZnO:Nd0.006,Li0.006. [Figure 4] FIG. 2 is an explanatory diagram showing the fluorescence and excitation spectra of ZnO:Nd0.006,Li0.006. [Diagram 5] FIG. 13 is an explanatory diagram showing stress-luminescence characteristics against a compressive load. [Figure 6] FIG. 11 is an explanatory diagram showing a state of frictional luminescence. [Figure 7] FIG. 13 is an explanatory diagram showing the stress-luminescence intensity when the measurement is repeated. [Figure 8] FIG. 1 is an explanatory diagram showing stress-induced luminescence intensity under various conditions. [Figure 9] FIG. 1 is an explanatory diagram showing the PL·ML intensities of ZnO:Ndy,Li0.01 versus the amount of Nd added. [Figure 10] FIG. 1 is an explanatory diagram showing the PL·ML intensities of ZnO:Nd0.006,Lix versus the amount of Li added. [Figure 11] FIG. 1 is an explanatory diagram showing the PL·ML intensities of ZnO:Nd0.006,Lix versus the amount of Li added. [Figure 12] FIG. 2 is an explanatory diagram showing an XRD spectrum. [Figure 13] FIG. 1 is an explanatory diagram showing the effect of additives on ML and PL intensities. [Figure 14] FIG. 2 is an explanatory diagram showing an XRD spectrum of a stress-stimulated luminescent material obtained by a urea liquid phase method. [Figure 15] FIG. 2 is an explanatory diagram showing an SEM image of a stress-stimulated luminescent material obtained by a urea liquid phase method. [Figure 16] FIG. 1 is an explanatory diagram showing the PL·ML intensities versus Zn concentration of a mechanoluminescent material obtained by a urea liquid phase method. [Figure 17] FIG. 2 is an explanatory diagram showing an XRD spectrum of a stress-stimulated luminescent material obtained by a thioacetamide liquid phase method. [Figure 18] FIG. 2 is an explanatory diagram showing an SEM image of a stress-stimulated luminescent material obtained by a thioacetamide liquid phase method. [Figure 19] FIG. 2 is an explanatory diagram showing PL spectra in the presence or absence of alkali metal ions and in both liquid phase methods. [Figure 20] FIG. 1 is an explanatory diagram showing the structures of zinc hydroxide and zinc sulfide. [Figure 21] FIG. 2 is an explanatory diagram showing XRD diffraction patterns (30-40°) of ZnO:Nd0.006,Li0.006 at each firing temperature. [Figure 22] FIG. 1 is an explanatory diagram showing the firing temperature dependence of ML and PL intensities. [Figure 23] FIG. 2 is an explanatory diagram showing the firing temperature dependence of ML center luminescence of alkali metal elements. [Figure 24] FIG. 1 is an explanatory diagram showing the presence or absence of mechanoluminescence when the Li ion concentration is changed in ZnO:Lix,Nd0.006. [Diagram 25] FIG. 1 is an explanatory diagram showing the presence or absence of mechanoluminescence when the Li concentration and Nd concentration are changed in ZnO:Lix,Ndy. [Figure 26] FIG. 1 is an explanatory diagram showing the presence or absence of stress-stimulated luminescence when Li and Ba ions are added as co-doped ions. [Figure 27] FIG. 13 is an explanatory diagram showing the presence or absence of stress-stimulated luminescence when Na ions or K ions are used as co-doped ions. [Figure 28] FIG. 1 is an explanatory diagram showing the presence or absence of stress-induced luminescence when other element ions are added together with Nd ions as luminescence center ions. [Figure 29] FIG. 1 is an explanatory diagram showing the presence or absence of stress-stimulated luminescence when the concentration of added Nd ions, Yb ions, or Tb ions is changed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The present invention relates to a stress-stimulated luminescent material that emits luminescence correlated with the energy of an external mechanical stimulus, and relates to a stress-stimulated luminescent material having ZnO (zinc oxide) as a base material.

[0032] In particular, the stress-stimulated luminescent material according to this embodiment is characterized in that it is made of ZnO in which luminescence center ions and predetermined co-doped ions are dissolved in solid solution.

[0033] The solid solution of the predetermined co-doped ions or luminescence center ions in ZnO may be a substitutional solid solution or an interstitial solid solution.

[0034] In addition, the predetermined co-doped ions to be dissolved in ZnO are not particularly limited, but may be, for example, silver ions, aluminum ions, or alkali metal ions. The alkali metal ions may be ions of any one or more metals selected from alkali metals, that is, Li (lithium), Na (sodium), K (potassium), Rb (rubidium), Cs (cesium), and Fr (francium). In particular, if the alkali metal ions are ions of at least one element selected from Li, Na, K, Rb, and Cs, and Nd ions are selected as the luminescence center ions, a stress-stimulated luminescent material with more reliable luminescence can be obtained.

[0035] The luminescence center ion to be dissolved in ZnO is not particularly limited as long as it is an ion that can be dissolved in ZnO together with the above-mentioned co-doped ion and function as a luminescence center. For example, it can be an ion of at least one metal selected from transition metals and rare earths.

[0036] Here, the transition metal ion can be understood as an ion of a transition metal present between the elements of Groups 3 and 11.

[0037] Furthermore, rare earth (rare earth metal) ions can be understood to be, for example, ions of Sc (scandium), Y (yttrium), La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium).

[0038] Among ions of metals belonging to the transition metals and rare earths, when Nd ions are used as the luminescence center ions to be solid-dissolved in ZnO, by adding co-doped ions as described above and by using ions of at least one element selected from Ag, Al, Li, Na, K, Rb, and Cs as the co-doped ions, a mechanoluminescent material with more reliable luminescence can be obtained.

[0039] The stress-stimulated luminescent material according to the present embodiment has such a configuration, and can be a stress-stimulated luminescent material having ZnO as a host material. In other words, the stress-stimulated luminescent material according to the present embodiment can be said to be a stress-stimulated luminescent material containing a ZnO crystal in which co-doped ions and luminescence center ions are dissolved.

[0040] The mechanoluminescent material according to this embodiment is represented by the general formula ZnO:E x M y (wherein E is a predetermined co-doped ion, and M is a luminescent center ion which is at least one metal ion selected from a transition metal ion and a rare earth ion), and x=0.0001 to 0.7, and y=0.001 to 0.2.

[0041] In addition, the general formula Zn 1-x E x O:M y(However, E is a predetermined co-added ion, and M is a luminescence center ion which is at least one kind of metal ion selected from transition metal ions and rare earth ions.) It has a composition represented by, and it may be that x = 0.0001 to 0.7 and y = 0.001 to 0.2. Furthermore, Zn 1-y M y O:E x (However, E is a predetermined co-added ion, and M is a luminescence center ion which is at least one kind of metal ion selected from transition metal ions and rare earth ions.) It has a composition represented by, and it may be that x = 0.0001 to 0.7 and y = 0.001 to 0.2.

[0042] Here, adding the co-added ion in an amount exceeding 0.7 for x is not preferable because almost no further effect can be expected. Also, the lower limit of x is, for example, 0.0001 or more to obtain firm stress luminescence characteristics, but it has been clarified from the experience of the present inventor that stress luminescence is still possible even below this. That is, the range of x may be 0 < x ≤ 0.7, and by setting 0.0001 ≤ x ≤ 0.7, luminescence corresponding to stress can be more firmly generated.

[0043] Similarly for y, when y is less than 0.001, it is not preferable because almost no effect of adding the luminescence center ion can be obtained. By setting 0.001 ≤ y ≤ 0.2, luminescence corresponding to stress can be more firmly generated.

[0044] In addition, it should be noted that the stress luminescence material of this embodiment represented by the above general formula is such that with respect to Zn contained in ZnO as the matrix material, the co-added ion is solid-solved at a concentration corresponding to 0.01 to 70 mol%, and the luminescence center ion is 0.1 to 20 mol%, preferably 0.1 to 12 mol%, more preferably 0.1 to 1.2 mol%.

[0045] The stress-stimulated luminescent material according to the present embodiment may be dispersed in a predetermined matrix material to form a stress-stimulated luminescent body. For example, by dispersing a powdered stress-stimulated luminescent material in a resin having a curing property as the matrix material and curing the resin, a stress-stimulated luminescent body of a desired shape that emits light when stress is applied can be easily formed. The matrix material used is one that is at least permeable to excitation light for exciting the stress-stimulated luminescent material mixed in the matrix material and fluorescence emitted from the stress-stimulated luminescent material.

[0046] In addition, the stress-stimulated luminescent material is not limited to a solid, and may be a liquid having flowability. Specifically, paint containing the stress-stimulated luminescent material according to the present embodiment is also included in the concept of the stress-stimulated luminescent material.

[0047] The present invention also provides a method for producing a mechanoluminescent material using ZnO as a host material. There are two methods for producing the material: a solid-phase reaction method and a liquid-phase reaction method.

[0048] In the method for producing a stress-stimulated luminescent material using ZnO as a base material according to the present embodiment as a solid-state reaction method, a zinc compound, a compound of at least one metal selected from transition metals and rare earths, and a predetermined co-doped ion supplying compound are mixed and fired. In the following description, the method for producing a stress-stimulated luminescent material using ZnO as a base material according to the present embodiment by the solid-state reaction method is also referred to as the "solid-state method according to the present embodiment."

[0049] Here, the zinc compound is not particularly limited as long as it is a compound that can form ZnO crystals, i.e., a hexagonal wurtzite crystal structure as shown in FIG. 1, through mixing and firing processes, and can be, for example, ZnO, ZnS, etc.

[0050] The co-additive ion supply compound may be a compound capable of dissolving the co-additive ions described above in the ZnO crystal. The co-additive ion supply compound is not particularly limited, but if one dares to give an example, it may be a silver ion supply compound capable of dissolving silver ions in the ZnO crystal, an aluminum ion supply compound capable of dissolving aluminum ions, or an alkali metal compound. The alkali metal compound may be a compound capable of dissolving alkali metal ions in the ZnO crystal, for example, an alkali metal carbonate, an alkali metal nitrate, an alkali metal chloride, or the like. More specifically, for example, when Li is selected as the alkali metal, it may be Li2CO3, LiNO3, LiCl, or the like, when Na is selected, it may be Na2CO3, NaNO3, NaCl, or the like, and when K is selected, it may be K2CO3, KNO3, KCl, or the like.

[0051] In addition, the compound of at least one metal selected from transition metals and rare earths is not particularly limited as long as it is a compound capable of dissolving at least one metal ion selected from transition metal ions and rare earth ions as luminescence center ions in ZnO crystals, and oxides and salts (chlorides, nitrates, carbonates, etc.) of the same metals can be used. More specifically, for example, when Nd is selected, Nd2O3, NdCl3, Nd(NO3)3·6H2O, etc. can be used. In the following description, the compound that supplies the luminescence center ion, that is, the compound of at least one metal selected from transition metals and rare earths, is also referred to as the "luminescence center supplying compound."

[0052] It is not necessary to use separate compounds for each of the above-mentioned compounds, and if there is a compound containing any two of the elements, such a compound can also be used.

[0053] Then, these compounds are weighed out in predetermined amounts, thoroughly mixed in a mortar or the like, and then fired. If necessary, the fired product is pulverized to obtain the mechanoluminescent material according to this embodiment.

[0054] The weighing of each compound can be based on the composition ratio of the stress-stimulated luminescent material according to this embodiment, and the amount of ZnO necessary to form the base material, the amount of the co-additive ion supplying compound capable of dissolving co-additive ions equivalent to 0.01 to 70 mol % of Zn contained in the ZnO, and the amount of the luminescent center supplying compound capable of dissolving luminescent center ions equivalent to 0.1 to 20 mol %, preferably 0.1 to 12 mol %, and more preferably 0.1 to 1.2 mol % of Zn, may be weighed and mixed.

[0055] In the method for producing a stress-stimulated luminescent material using ZnO as a base material according to the present embodiment, the firing is preferably performed in an oxidizing atmosphere. Generally, firing for preparing a stress-stimulated luminescent material is performed under oxygen-free conditions such as a nitrogen gas atmosphere or an inert gas atmosphere. In this respect, the solid-phase method according to the present embodiment is characterized in that a stress-stimulated luminescent material with good luminescence properties can be obtained by firing in an oxidizing atmosphere, for example, in air (atmosphere).

[0056] In particular, the near-infrared stress-luminescent materials known so far, such as Sr3Sn2O7:Nd 3+ While (SSN) and the like require firing at about 1500°C in a nitrogen atmosphere, the mechanoluminescent material according to the present embodiment, which uses neodymium ions as the luminescent center ion, is extremely useful in that it can be manufactured by firing in air, even though it is the same near-infrared mechanoluminescent material. Note that, as will be explained later with reference to data, firing in an oxidizing atmosphere is not an essential condition, since mechanoluminescent properties are observed even when firing in a deoxidized environment. However, this does not prevent the applicant from limiting the firing conditions when granting the patent of this application.

[0057] According to the solid phase method of this embodiment, a method for producing a stress-stimulated luminescent material using ZnO as a base material by a solid phase reaction method can be provided.

[0058] This application also provides a manufacturing method by a liquid phase reaction method. That is, in the manufacturing method of the stress-stimulated luminescent material using ZnO as a base material according to this embodiment, the liquid property of a zinc ion-containing aqueous solution in which a luminescent center ion and a predetermined co-doped ion are present is made basic, or a sulfide is reacted with the aqueous solution, so that the co-doped ion and the luminescent center ion are coprecipitated with zinc hydroxide or zinc sulfide, and the coprecipitate is fired. In the following description, the manufacturing method of the stress-stimulated luminescent material using ZnO as a base material according to this embodiment by the liquid phase reaction method is also referred to as the "liquid phase method according to this embodiment."

[0059] The aqueous solution used in the liquid phase method according to this embodiment contains zinc ions for forming the base material, and further contains co-doped ions and luminescent center ions.

[0060] The preparation of the aqueous solution requires a zinc compound which is a supply source of zinc ions, a co-additive ion supplying compound which is a supply source of co-additive ions, and a luminescence center supplying compound which is a supply source of luminescence center ions. These compounds are not particularly limited as long as they are water-soluble and can be coprecipitated, and further, a mechanoluminescent material in which the co-additive ions and the luminescence center ions are solid-solved in the ZnO crystals can be prepared by firing the coprecipitated product.

[0061] As the zinc compound, a compound that is water-soluble and capable of liberating zinc ions is suitable, and for example, zinc salts, more specifically ZnCl2, etc. can be used.

[0062] As the co-additive ion supplying compound, a compound that is water-soluble and can liberate silver ions, aluminum ions, alkali metal ions, etc. is suitable. As the alkali metal compound, a compound that is water-soluble and can liberate alkali metal ions, for example, lithium ions, sodium ions, potassium ions, etc. is suitable, and for example, salts of alkali metals, more specifically LiCl, NaCl, KCl, etc. can be used.

[0063] As the luminescent center supplying compound, a compound that is water-soluble and can liberate a luminescent center ion, for example, a neodymium ion, is suitable. For example, a salt of at least one metal selected from transition metal ions and rare earth ions, more specifically, Nd(NO3)3·6H2O, etc. can be used.

[0064] The concentration of each ion in the aqueous solution derived from these compounds can be in accordance with the composition ratio of the stress-stimulated luminescent material according to this embodiment. That is, the aqueous solution may contain zinc ions necessary for constituting the base material, co-additive ions equivalent to 0.01 to 70 mol % of the zinc ions, and luminescence center ions equivalent to 0.1 to 20 mol %, preferably 0.1 to 12 mol %, more preferably 0.1 to 1.2 mol % of the zinc ions.

[0065] In addition, the liquid phase method according to this embodiment is characterized in that a precipitated zinc compound is generated and precipitated (co-precipitated) while involving the co-doped ions and the luminescent center ions.

[0066] The method for producing the precipitated zinc compound is not particularly limited, but may be, for example, by making the aqueous solution basic or by reacting the aqueous solution with a sulfide. When the aqueous solution is made basic, zinc hydroxide is produced and precipitated, and when the aqueous solution is reacted with a sulfide, zinc sulfide is produced and precipitated.

[0067] One example of a method for precipitating zinc hydroxide is a method using urea as a precipitant. More specifically, a predetermined amount of urea is dissolved in an aqueous solution, and the aqueous solution is heated to about 70 to 90°C to decompose the urea, i.e., CO(NH2)2+ H2O → 2NH3+ CO2 This is a way to encourage this.

[0068] In the presence of zinc chloride, CO(NH2)2+ ZnCl2+ 3H2O → Zn(OH)2↓ + 2NH4Cl + CO2 The reaction takes place, and zinc hydroxide precipitates. At this time, the co-additive ions and luminescent center ions present in the aqueous solution can be caught in the precipitation (co-precipitation).

[0069] Another example of a method for precipitating zinc hydroxide is to use thioacetamide as a precipitant. More specifically, a certain amount of thioacetamide is dissolved in an aqueous solution, and the aqueous solution containing zinc chloride is heated to 70°C or higher to promote decomposition of the thioacetamide. C2H5NS + ZnCl2+ H2O → ZnS↓ + C2H5NO + 2HCl The reaction takes place, and zinc sulfide precipitates. The co-doped ions and luminescent center ions present in the aqueous solution can be caught in the precipitate (co-precipitation).

[0070] In the liquid phase method, the concentration of Zn ions in the aqueous solution can be in the range of 0.1 to 0.5 mol / L.

[0071] The concentration of the alkali metal ions in the aqueous solution can be set to an amount equivalent to 0.01 to 70 mol % of the Zn ions contained in a unit volume, that is, in the range of 0.00001 to 0.35 mol / L.

[0072] The concentration of the luminescent center ion in the aqueous solution corresponds to 0.1 to 20 mol%, preferably 0.1 to 12 mol%, and more preferably 0.1 to 1.2 mol% of the Zn ions contained in a unit volume, and for example, in the case of 0.1 to 1.2 mol%, the concentration can be in the range of 0.0001 to 0.006 mol / L.

[0073] The amount of the precipitant in the aqueous solution can be adjusted as appropriate, but as an example, it can be an amount that can react with Zn ions and precipitate them sufficiently. For example, when urea (CO(NH2)2) or thioacetamide (C2H5NS) is used as the precipitant, the amount can be about 1 mol, preferably a little more than 1 mol (for example, about 1.1 to 1.5 mol), per mol of Zn ions.

[0074] The obtained coprecipitate is calcined, and the calcined product is pulverized as necessary, to obtain the mechanoluminescent material according to this embodiment.

[0075] In the liquid phase method according to this embodiment, firing is performed in an oxidizing atmosphere, for example, in air (atmosphere), in the same manner as in the solid phase method according to this embodiment described above, to obtain a mechanoluminescent material with good luminescence properties. Note that firing in an oxidizing atmosphere is not essential in the liquid phase method according to this embodiment, and the applicant is free to limit the firing conditions.

[0076] The present application also provides a method for making ZnO into a stress-stimulated luminescent material by dissolving co-doped ions and luminescent center ions in ZnO. That is, the present application provides a method for making ZnO into a stress-stimulated luminescent material, which has been a material that could not be made to function as a stress-stimulated luminescent material up until now, and is characterized by dissolving co-doped ions and luminescent center ions in ZnO.

[0077] The following will describe in detail the stress-stimulated luminescent material and stress-stimulated luminescent body according to the present embodiment, the method for producing the stress-stimulated luminescent material, and the method for producing a stress-stimulated luminescent material from ZnO, with reference to actual production examples and test results, etc. Note that, although the present application will clarify the contents of the present invention with some representative examples, it should be noted that, based on the inventor's many years of experience, stress-stimulated luminescence is possible within the range of elements and values ​​shown in the general formula, and the present invention is not limited to the elements and values ​​of the representative examples.

[0078] [1. Preparation of mechanoluminescent materials by solid-state method] The solid-state reaction method according to this embodiment produces a ZnO:Nd 3+ 0.006 ,Li + 0.006 The following was prepared.

[0079] First, ZnO (Sakai Chemical, 99.7%) as a zinc compound, Li2CO3 (Kojundo Chemical Laboratory, 99.99%) as an alkali metal compound (co-doped ion supply compound), and Nd2O3 (Kojundo Chemical Laboratory, 99.9%) as a luminescent center supply compound were weighed out based on the stoichiometric ratio, and then thoroughly mixed and ground in an agate mortar.

[0080] Next, the crushed mixture was sintered by firing it in an air atmosphere at temperatures of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, and 1200°C for a predetermined time (for example, 3 to 10 hours, more specifically, 4 to 6 hours) in an electric furnace. The resulting fired product was crushed in an agate mortar to obtain ZnO:Nd 3+ 0.006 ,Li + 0.006 In the following description, the above-mentioned production method is also referred to as a solid-phase based production method.

[0081] Further, here, samples in which the amount of co-added ion supply compound added was changed relative to the solid phase standard manufacturing method, and samples in which the amount of luminescence center supply compound added was changed were also prepared.

[0082] The samples in which the amount of the alkali metal compound added as the co-doped ion supply compound was changed were samples in which the amount of Li added was changed from 0 to 70 mol%. 3+ 0.006 ,Li + x (x=0~0.7), more specifically, the samples were prepared for x=0, 0.001, 0.002, 0.003, 0.004, 0.006, 0.012, 0.018, 0.05, 0.1, 0.2, 0.4, 0.5, and 0.7.

[0083] The samples in which the amount of the luminescence center supplying compound was changed were samples in which the amount of Nd added was changed from 0 to 1.2 mol%. 3+ y ,Li + 0.01(y=0 to 0.12), and more specifically, the compositions were prepared for y=0, 0.003, 0.006, and 0.012.

[0084] In addition, samples were prepared using ZnS (Wako Pure Chemical Industries, 99.999%) instead of ZnO, which was used as the zinc compound in the solid-phase standard method. In the following explanation, this method is also called the solid-phase ZnS method.

[0085] In addition, samples were prepared using LiCl (CERAC 99.8%), Na2CO3 (Kojundo Chemical Laboratory 99.8%), K2CO3 (Kojundo Chemical Laboratory 99%), MgCO3 (Kojundo Chemical Laboratory 99.9%), CaCO3 (Kojundo Chemical Laboratory 99.99%), SrCO3 (Kojundo Chemical Laboratory 99.99%), BaCO3 (Kojundo Chemical Laboratory 99.95%), and H3BO3 (ALDRICH 99.99%) instead of Li2CO3, an alkali metal compound used as a co-additive ion supply compound in the solid-phase standard manufacturing method. The amount of each target element was adjusted to 1 mol% in the prepared samples.

[0086] In addition, with regard to the firing under air atmosphere in the solid-phase standard manufacturing method, samples were also prepared in which the firing atmosphere was a N2 atmosphere or a flowing Ar atmosphere.

[0087] 2. XRD Analysis of Stimuli-Luminescent Materials The crystal phases of the samples obtained by the solid-phase standard method and the solid-phase ZnS method were identified using a powder X-ray diffraction (XRD) analyzer. 3+ 0.006 ,Li + 0.006 4 shows the XRD diffraction pattern of

[0088] As shown in Figure 2, the sample obtained by the solid-phase standard method was found to be a single-phase hexagonal zinc oxide (ZnO) (PDF_01-078-3322) by XRD measurement.

[0089] In addition, the analysis of samples obtained by the solid-phase ZnS manufacturing method confirmed that when ZnS was used as the raw material, the crystallinity improved and the (101) plane orientation was observed. This was thought to be due to the fact that ZnS has a lower melting point than ZnO, as well as the influence of changes in the crystal structure during oxidation.

[0090] As shown in Figure 1, ZnO has a structure classified as space group P63mc without a center of symmetry. The tetrahedron with Zn at the center forms a plate-like structure. This easily distorted structure is thought to be advantageous for mechanoluminescence.

[0091] 3. Microscopy of Stimuli-Luminescent Materials Next, the samples obtained by the solid-phase reference method and the solid-phase ZnS method were observed using a scanning electron microscope. Figure 3(a) shows an SEM image of the sample obtained by the solid-phase reference method, and Figure 3(b) shows an SEM image of the sample obtained by the solid-phase ZnS method.

[0092] As can be seen from the SEM image shown in Figure 3(a), the ZnO particles obtained by the solid-phase based method (synthesized based on ZnO) were amorphous and had a shape resembling an aggregate of particles of about 1 μm in size, with some of them having a layered structure.

[0093] In contrast, the ZnO particles obtained by the solid-phase ZnS method (synthesized based on ZnS) had an irregular but smooth surface, as shown in Figure 3(b), and a striped pattern was observed.

[0094] 4. Fluorescence and Excitation Spectrum Measurement Next, the fluorescence spectrum and excitation spectrum were measured for the sample obtained by the solid-phase standard preparation method. The fluorescence spectrum was measured using a spectrometer. The measurement result of the fluorescence spectrum is shown in Figure 4(a), and the measurement result of the excitation spectrum is shown in Figure 4(b).

[0095] As can be seen from FIG. 4(a), the ZnO:Nd 3+ 0.006,Li + 0.006 898 nm 4 F 3 / 2 → 4 I 9 / 2 , 1086 nm 4 F 3 / 2 → 4 I 11 / 2 It was confirmed that the compound exhibited near-infrared photoluminescence (PL) based on the photocatalytic activity of ZnO. Furthermore, this PL was much stronger than the fluorescence in the visible region.

[0096] Furthermore, as shown in Figure 4(b), it was shown that their PL could be excited by ultraviolet and visible light.

[0097] 5. Study of mechanoluminescence properties Next, ZnO:Nd obtained by the solid-phase standard method 3+ 0.006 ,Li + 0.006 Regarding this, we investigated the properties of mechanoluminescence (ML).

[0098] The evaluation of the mechanoluminescence properties was carried out on a cylindrical specimen. This specimen was made of a composite resin pellet (diameter 25 mm, thickness 10 mm) made by mixing 0.5 g of the powder sample obtained by the solid-phase standard manufacturing method with 4.5 g of epoxy resin, and corresponds to the mechanoluminescent material according to this embodiment.

[0099] The specimen was pre-irradiated with excitation light for 5 minutes, waited for 10 seconds, and then mechanically compressed for evaluation. The light source used for pre-irradiation was an LED (MDRL-CUV31, MORITEX, Saitama, Japan) with a central wavelength of 365 nm (λ1 / 215 nm).

[0100] The specimens were compressed at 3 mm / min and 0 to 1000 N using a compression machine (Tensilon, RTC-1310A, Orintec Co., Tokyo, Japan). The ML strength of the upper and central parts of the specimens was measured using a camera equipped with an InGaAs sensor (C14041-10U, HAMAMATSU, Shizuoka, Japan). The results are shown in Figure 5.

[0101] As can be seen from FIG. 5, the ZnO:Nd 3+ 0.006 ,Li + 0.006 It was confirmed that the mechanoluminescence intensity at the center of the test specimen (ROI 2) increased according to the applied force from 0 to 500 N.

[0102] On the other hand, the upper end of the test specimen (ROI 1) exhibited a sudden mechanoluminescence up to 200 N, after which the amount of luminescence tended to decrease. This indicates that the upper end of the cylindrical test specimen was subjected to extremely strong stress, and therefore had a strong effect of destructive luminescence.

[0103] Furthermore, as shown in Figure 6, when letters were written on the flat surface of the test specimen using a glass rod, near-infrared triboluminescence was observed along the path of the letters.

[0104] Next, the same test was repeated 20 times in succession on the test specimen, and the mechanoluminescence intensity was checked for each test. The results are shown in Figure 7.

[0105] As can be seen from Fig. 7, the intensity of mechanoluminescence in the center of the specimen (ROI 2) did not show any significant change between the first and twentieth times, and stable mechanoluminescence was observed. 3+ 0.006 ,Li + 0.006 This is evidence of piezoluminescence, which is light emission in the elastic region.

[0106] On the other hand, the upper end of the pellet (ROI 1) contained destructive luminescence, and therefore, it was shown that the quantification was not high.

[0107] In this way, it has been shown that the mechanoluminescent material according to this embodiment is a mechanoluminescent material having ZnO as a host material. In particular, this is the first time that mechanoluminescence has been found having ZnO as a host material, and in this respect, the present invention is of great significance.

[0108] [6. Comparison of mechanoluminescence intensity between samples obtained by the solid-phase standard method and other samples] Next, the mechanoluminescence intensity of the sample obtained by the solid-phase reference method was compared with that of other samples. The five samples used for comparison were: [A] a sample obtained by the solid-phase reference method, [B] a sample obtained by the solid-phase ZnS method, [C] a sample prepared in the same manner as the solid-phase reference method without adding an alkali metal compound (a co-additive ion supply compound), [D] a sample prepared in the same manner as the solid-phase reference method except that it was fired under an argon atmosphere, and [E] a sample prepared in the same manner as the solid-phase reference method except that it was fired under a nitrogen atmosphere. All samples used here were fired at 1100°C.

[0109] A graph of the mechanoluminescence intensity of each sample is shown in Figure 8. In the graph of Figure 8, [F] indicates the mechanoluminescence intensity in the visible region of the sample obtained by the solid-phase standard manufacturing method.

[0110] First, it was confirmed that the mechanoluminescence intensity was improved by about 1.5 times in the case of the solid-phase ZnS manufacturing method, as shown by [B] in Figure 8. This is thought to be because, as shown by the XRD spectrum in Figure 2, the crystallinity is improved when ZnS is used as the zinc compound.

[0111] Furthermore, as shown by [C], when no alkali metal compound (co-doped ion supply compound) was added, very little mechanoluminescence was observed, but the mechanoluminescence intensity was significantly reduced. This shows that the addition of a co-doped ion supply compound is important in endowing ZnO with mechanoluminescent properties. In addition, it can be said that the addition of a co-doped ion supply compound is essential to realize a ZnO-based mechanoluminescent material with practical utility.

[0112] Moreover, as shown in [D] and [E], when the sintering was performed in an Ar or N2 atmosphere, a significant decrease in the mechanoluminescence intensity was observed, although not as much as in [C]. This is thought to be due to the fact that oxygen defects in ZnO are deeply related to the loss of the mechanoluminescence properties. In other words, although not essential, it is clear that sintering in an atmosphere containing oxygen, such as in the air, is important in realizing a ZnO-based mechanoluminescent material with good mechanoluminescence intensity.

[0113] As shown by [F], no mechanoluminescence was observed in the visible region (Wavelength 400-800 nm) when the sample obtained by the solid-phase standard manufacturing method [A] was observed. However, this result is for a sample sintered at 1100°C, and the inventor's experience has shown that luminescence is observed in the visible region when sintered at other temperatures. Although the data is omitted, in fact, mechanoluminescence in the visible region was observed in a sample sintered at 900°C using the same method as the solid-phase standard manufacturing method.

[0114] [7. Examination of the amount of luminescence center ions] Next, in order to study the optimization of the manufacturing conditions for the stress-stimulated luminescent material, the amount of the luminescence center ion was first examined.

[0115] Specifically, the ZnO:Nd 3+ y ,Li + 0.01 The mechanoluminescence intensity was measured for (y=0, 0.003, 0.006, 0.012), and the results are shown in Figure 9.

[0116] As can be seen from Fig. 9, both photoluminescence and stress luminescence are due to the luminescence of luminescence center ions (here, Nd 3+ ). Therefore, when the Nd addition amount was 0 mol%, no luminescence was shown. In contrast, for ZnO:Nd 3+ y ,Li + 0.01 (y = 0.003, 0.006, 0.012), stress luminescence was observed, but no clear correlation with the addition amount could be confirmed. Although the illustration of the data is omitted, neither photoluminescence nor stress luminescence showed a significant effect when added in the range of y = 0.001 to 0.12 (0.1 to 12 mol%). Also, stress luminescence was observed even in the range of 0 < y < 0.001.

[0117] [8. Examination of the amount of co - added ions] Next, the amount of co - added ions was examined. Specifically, the stress luminescence intensity of ZnO:Nd 3+ 0.006 ,Li + x (x = 0, 0.001, 0.002, 0.003, 0.004, 0.006, 0.012, 0.018, 0.05, 0.1, 0.2, 0.4, 0.5, 0.7) prepared in [1. Preparation of stress luminescence material by solid - phase method] was measured. The results are shown in Fig. 10.

[0118] First, regarding x = 0, 0.001, 0.002, 0.003, 0.004, 0.006, 0.012, 0.018 (0 to 1.8 mol%), as can be seen from Fig. 10, when the addition amount of co - added ions (here, Li ions which are alkali metal ions) was 0 mol%, no stress luminescence characteristics were shown. On the other hand, stress luminescence was observed for subsequent additions, but no correlation with the addition amount of co - added ions was seen. This suggests that traps are generated by the addition of co - added ions, which is a major factor in having stress luminescence characteristics.

[0119] In addition, for x = 0.05, 0.1, 0.2, 0.4, 0.5, and 0.7 (5 to 70 mol%), as shown in Figure 11, stress-stimulated luminescence was observed in response to the addition of co-doped ions, but no correlation with the amount of added ions was observed.

[0120] From these results, it was found that the addition of co-doped ions is an essential element for the mechanoluminescent properties of the mechanoluminescent material according to this embodiment. 3+ 0.006 ,Li + x The results of XRD measurement when the amount of co-doped ions (here, Li ions, which are alkali metal ions) added is 0 to 1.8 mol% are shown in Fig. 12(a), and the results of XRD measurement when the amount is 5 to 70 mol% are shown in Fig. 12(b). From these XRD measurement results, no change in the zinc oxide crystal phase due to the addition of co-doped ions was confirmed. However, according to further research by the present inventors, although detailed data will not be presented here, a change in lattice constant due to the addition of Li was observed, and it was found that Li substituted the Zn site.

[0121] Next, in order to consider the significance of the addition of co-additive ions, several alkali metal compounds, alkaline earth metal compounds, and boric acid were added and compared.

[0122] [9. Consideration of the type of co-doped ions] Here, we investigated the types of co-doped ions. Specifically, we investigated the photoluminescence and mechanoluminescence properties of samples prepared using various compounds in [1. Preparation of mechanoluminescent material by solid-state method], that is, samples using LiCl, Na2CO3, K2CO3, MgCO3, CaCO3, SrCO3, BaCO3, and H3BO3 instead of Li2CO3, an alkali metal compound used as a co-doped ion supply compound in the solid-state standard method. The results are shown in Figure 13.

[0123] As can be seen from FIG. 13, the highest luminescence intensity for both photoluminescence and mechanoluminescence was obtained when, among the compounds used this time, the alkali metal ion was lithium ion and Li2CO3 was used as the alkali metal compound.

[0124] In contrast, when the co-doped ion was the lithium ion but the alkali metal compound used was a chloride, or when the co-doped ion was a sodium ion or potassium ion, a slight decrease in ML / PL intensity was observed.

[0125] Also, it should be noted that the ML / PL characteristics were not observed in the samples using other compounds, namely, the samples using MgCO3, CaCO3, SrCO3, BaCO3, and H3BO3.

[0126] Considering this point, one of the reasons why alkali metal elements have luminescence properties is that their charge is 1+. That is, Nd is in the 3+ state and Zn is in the 1+ state. 2+ Since it is thought that the alkali metal element is suitable for the role of charge compensation, this effect cannot be obtained when other compounds are used, so Nd 3+ may not have been successfully substituted.

[0127] From this, it can be said that in order for ZnO to have mechanoluminescence properties, the addition of a co-doping element that plays a role in charge compensation is essential, and that the effect of this is extremely large.

[0128] 10. Preparation of mechanoluminescent materials by liquid phase method Next, the mechanoluminescent material according to the present embodiment was prepared by the liquid phase reaction method according to the present embodiment.

[0129] The raw material zinc compound ZnCl2 (Wako Pure Chemicals, 98%), the luminescence center supply compound Nd(NO3)3·6H2O (Wako Pure Chemicals, 99.5%), and the alkali metal compound LiCl (CERAC, 99.8%) were added as the co-additive ion supply compound, and an aqueous solution of any concentration was prepared using ion-exchanged water. In this section, the Zn ion concentration in the aqueous solution was changed from 0.025 to 0.1 mol / L, the Nd ion concentration was changed to 0.5 mol% relative to the Zn ion, and the Li ion concentration was changed to 0 to 2.4 mol% relative to the Zn ion.

[0130] In addition, CO(NH2)2 (Wako Pure Chemical Industries, 99.9%) and CH3CSNH2 (Wako Pure Chemical Industries, 99.8%) were selected as precipitants and added in the same amount as the Zn concentration.

[0131] The synthesis was carried out using an autoclave, and hydrothermal synthesis was carried out at a temperature of 95°C for 24 hours. The obtained precipitate was filtered by suction and dried at 70°C for 3 hours. Next, using an electric furnace, the crushed mixture was fired in an air atmosphere at temperatures of 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, and 1200°C for a predetermined time (for example, 3 to 10 hours, more specifically 4 to 6 hours) for sintering. The obtained fired product was crushed in an agate mortar, and sample evaluation was carried out.

[0132] Next, a method for producing a mechanoluminescent material using urea (CO(NH2)2) as a precipitant will be described. First, regarding the reaction in the liquid phase method according to this embodiment, urea in an aqueous solution starts to hydrolyze at 70 to 80°C, and decomposition progresses rapidly at 90°C or higher. Ammonia is highly soluble in water and is basic.

[0133] On the other hand, ZnCl2 in aqueous solution is Zn 2+ In the liquid phase, it is precipitated as Zn(OH)2 under basic conditions. When Zn(OH)2 precipitates, the surrounding Nd 3+ Or Li + It often occurs when ions such as these are involved in precipitation (coprecipitation).

[0134] Therefore, in the liquid phase to which urea has been added as a precipitant, it can be extracted as a precipitate of Zn(OH)2 by heating to 70°C or higher. In addition, if the entire liquid phase is at a uniform temperature, it is thought that ions such as urea and zinc are also uniformly dispersed. Therefore, the system present in the obtained precipitate becomes a uniform solid phase.

[0135] The obtained Zn(OH)2 is oxidized by baking at 800°C or higher to become ZnO. At this time, if the temperature is low enough, the ZnO can be formed while maintaining its particle shape, so ZnO of any particle shape can be obtained. In the following description, the liquid phase method according to this embodiment using urea as a precipitant is also referred to as the "urea liquid phase method according to this embodiment."

[0136] Next, we will describe a method for producing a stress-stimulated luminescent material using thioacetamide (CH3CSNH2) as a precipitating agent.

[0137] Thioacetamide in aqueous solution hydrolyzes at temperatures above 70°C, releasing hydrogen sulfide. 2+ The ions react with hydrogen sulfide and precipitate as ZnS. At this time, like the urea described above, surrounding ions are involved and precipitated in a uniform state. ZnS becomes ZnO when fired at 800°C or higher. Therefore, ZnO particles that maintain any shape can be obtained. In the following description, the liquid phase method according to this embodiment using thioacetamide as a precipitant is also referred to as the "thioacetamide liquid phase method according to this embodiment."

[0138] [11. XRD analysis of mechanoluminescent materials obtained by urea liquid phase method] The crystal phase of the sample obtained by the urea liquid phase method according to this embodiment was identified by a powder X-ray diffractometer (XRD). Figure 14 shows the XRD diffraction patterns of the samples obtained by the liquid phase method using urea as a precipitant, with and without the presence of co-additive ions (here, Li ions, which are alkali metal ions) in the aqueous solution.

[0139] XRD measurements showed that all the synthesized materials were hexagonal zinc oxide (ZnO) single phase. Furthermore, ZnO doped with co-doped ions (alkali metal ions) showed a strong C-axis orientation.

[0140] [12. Microscopic examination of mechanoluminescent materials obtained by the urea liquid phase method] Next, in performing the liquid phase method using urea as a precipitant, we observed the samples obtained with and without the presence of co-additive ions (here, Li ions, which are alkali metal ions) in the aqueous solution using a scanning electron microscope. Figure 15(a) is an SEM image of a sample without co-additive ions, and Figure 15(b) is an SEM image of a sample with co-additive ions added.

[0141] As can be seen from Fig. 15(a), ZnO without co-doped ions was amorphous and had a variety of particle sizes ranging from 1 to 5 μm. In contrast, as shown in Fig. 15(b), ZnO with co-doped ions and C-axis orientation was layered particles, and this easily distorted shape is considered to be advantageous for mechanoluminescence.

[0142] [13. Study on ML / PL intensity as a function of Zn concentration] Next, the influence of changing the Zn concentration in the aqueous solution on the ML / PL intensity of the stress-stimulated luminescent material obtained by the urea liquid phase method according to this embodiment was examined. Fig. 16 is a graph showing the intensities of stress-stimulated luminescence and photoluminescence of the stress-stimulated luminescent material obtained by the urea liquid phase method when the Zn concentration in the aqueous solution is 0.1, 0.125, 0.3, and 0.5 mol / L. Note that in this graph, the PL / ML intensity of the sample obtained by the solid-phase reference method described above is taken as 100.

[0143] From the experience of the inventors, it is known that in the liquid phase method, if the Zn concentration is too high, precipitation occurs simultaneously in a short time, which tends to have a negative effect on particle shape control. Therefore, in this study, the Zn concentration was set to a maximum of 0.5 M, but the photoluminescence properties were found to be weaker at higher Zn concentrations.

[0144] In contrast, although no clear correlation with the Zn concentration could be confirmed, it was confirmed that mechanoluminescence was observed at Zn concentrations exceeding 0.1 M.

[0145] [14. XRD analysis of mechanoluminescent materials obtained by thioacetamide liquid phase method] The crystal phase of the sample obtained by the thioacetamide liquid phase method according to this embodiment was identified by a powder X-ray diffractometer (XRD). Figure 17 shows the XRD diffraction patterns of the samples obtained by the liquid phase method using thioacetamide as a precipitant, with and without the presence of co-additive ions (here, Li ions, which are alkali metal ions) in the aqueous solution.

[0146] As shown in Figure 17, when thioacetamide was used as a precipitant, a large change in the crystal structure of ZnO without co-added ions was observed compared to the case of the urea liquid phase method. When no co-added ions were added, the crystallinity improved, and strong orientation was observed in the (100) and (002) planes.

[0147] In contrast, when co-doped ions were added, the XRD spectrum was consistent with the hexagonal structure seen in solid-phase synthesis.

[0148] [15. Microscopic examination of mechanoluminescent materials obtained by the thioacetamide liquid phase method] Next, in performing the liquid phase method using thioacetamide as a precipitant, we observed the samples obtained with and without the presence of co-additive ions (here, Li ions, an alkali metal ion) in the aqueous solution using a scanning electron microscope. Figure 18(a) is an SEM image of a sample without co-additive ions, and Figure 18(b) is an SEM image of a sample with co-additive ions added.

[0149] As can be seen from FIG. 18(a), the particles without co-added ions were observed to have beautiful hexagonal columnar particles by SEM measurement.

[0150] In contrast, the ZnO particles synthesized by liquid phase and containing co-doped ions have a shape in which the hexagonal columnar particles are collapsed.

[0151] [16. Considerations regarding the two-phase method] Figure 19 shows the photoluminescence spectra of the mechanoluminescent materials obtained by both liquid phase methods. As can be seen from Figure 19, when no co-doped ions were added, Nd 3+ Since the substitution was not successful, almost no PL properties were observed.

[0152] In addition, ZnO synthesized by liquid phase synthesis using thioacetamide and co-doped ions showed slight PL properties, but the intensity was very weak.

[0153] Since the PL intensity is stronger when urea is used, it is expected that the precipitation probability of coexisting ions differs depending on the precipitant. Urea precipitates as zinc hydroxide, and thioacetamide precipitates as zinc sulfide, but it is thought that zinc hydroxide has a stronger ability to precipitate by involving surrounding ions due to its structure. The structure of zinc hydroxide is shown on the left in Figure 20, and zinc sulfide on the right.

[0154] [17. Effect of the sintering temperature in the solid-state method on mechanoluminescence intensity] We investigated the effect of the firing temperature in the solid-state method on mechanoluminescence intensity. 0.994 Nd 0.006 Li 0.006 The samples were prepared according to the standard solid-phase manufacturing method, except for the above. An Al2O3 crucible was used for firing, and the samples were sintered in air at temperatures between 900°C and 1300°C, or even higher temperatures up to 1500°C if necessary.

[0155] ZnO at each firing temperature 0.994 Nd 0.006 Li 0.006The XRD diffraction patterns of the above are shown in Figure 21. A single phase of ZnO (PDF_01-078-3322) was obtained at all firing temperatures. The XRD diffraction patterns showed a clear peak shift due to the change in firing temperature. The shift to the lower angle side is thought to be due to an increase in the lattice.

[0156] The sintering temperature dependence of ML and PL intensity was also recorded. As shown in Figure 22, both ML and PL were low at 900℃ and 1000℃, but both showed significantly higher values ​​at higher temperatures of 1100℃ and above. Note that when the sintering temperature was set to 1000℃, the ML (stimuli-luminescence intensity) was not 0, and light was emitted, albeit slightly.

[0157] In addition, for other alkali metal elements K and Na, experiments on the sintering temperature dependence were performed using the same method at temperatures set to 900°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, 1200°C, 1300°C, 1400°C, and 1500°C. As shown in Figure 23, when comparing ML center emission, it was found that the tendency was basically the same as that for Li. Note that the emission intensity for Li at a sintering temperature of 1000°C is not 0, and light is emitted, albeit slightly. Note that the previous Figure 22 is a graph normalized to the maximum value of 100, while Figure 23 shows a graph without normalization.

[0158] In addition, although the explanation showing the data is omitted, the mechanoluminescent material ZnO:Nd 3+ 0.006 ,Li + 0.006 Regarding the material, no stress-stimulated luminescence was observed at 600°C or 650°C, but stress-stimulated luminescence was observed at firing temperatures of 700°C or higher, and at temperatures between 900°C and 1500°C, the results were roughly the same as those of the stress-stimulated luminescent materials described above.

[0159] From these results, ZnO:Nd 3+It was shown that the ML strength is greatly improved by firing at 1100°C or higher and decreases at 1400°C or higher, and that the lower limit of the firing temperature is 700°C or higher, more preferably 900°C or higher, and even more preferably 1020°C or higher, and the upper limit of the firing temperature is 1500°C or lower, preferably 1400°C or lower, and more preferably 1300°C or lower, and that it is possible to produce a stress-stimulated luminescent material that exhibits stable stress-stimulated luminescence by firing at a temperature range that is a combination of any of these upper and lower limits.

[0160] 18. ZnO:Li x ,Nd 0.006 Presence or absence of mechanoluminescence when the Li ion concentration is changed at Next, ZnO:Li x ,Nd 0.006 The presence or absence of mechanoluminescence was confirmed when the concentration of the co-doped Li ions was changed from 0 to 0.7. The results are shown in Figure 24.

[0161] As can be seen from FIG. 24, when the value of x was set to 0, no mechanoluminescence was observed in the near-infrared region (>750 nm). However, when Li ions were added, mechanoluminescence was observed in the near-infrared region (>750 nm) up to a maximum value of x of 0.7.

[0162] 19. ZnO:Li x ,Nd y Presence or absence of mechanoluminescence when changing the Li concentration or Nd concentration at Next, ZnO:Li x ,Nd y The presence or absence of mechanoluminescence was confirmed when the concentration of the co-doped Li ions and the concentration of the luminescence center Nd ions were variously changed. The results are shown in Figure 25.

[0163] As can be seen from FIG. 25, mechanoluminescence was confirmed in the near-infrared region (>750 nm) for all of the materials.

[0164] [20. Whether or not mechanoluminescence occurs when Li and Ba ions are added as co-doped ions] Next, we investigated whether mechanoluminescence occurs when multiple co-doped ions are present. In particular, in this study, as a representative example, we used two types of co-doped ions, Li ion and Ba ion, and the luminescence center ion was Nd ion, and we fixed the concentrations of Li ion and Nd ion at 0.6 mol% and changed the concentration of Ba ion.

[0165] In addition, in the case of using only one type of co-doped ion or one type of luminescent center ion as in the past, ZnO:E x M y In the above, the formula is expressed as follows: x =E1 x1 ,E2 x2 , x = x1 + x2. For example, when there are three types of luminescent center ions, M y =M1 y1 ,M2 y2, M3 y3 , y = y1 + y2 + y3. In other words, in this study, E1 x1 =Li 0.006 , E2 x2 =Ba x2 , M y =Nd 0.006 The value of x2 was changed in the range of 0 to 0.05 to check whether or not mechanoluminescence occurred.

[0166] As a result, as shown in FIG. 26, in all of the materials in which the Ba ion concentration was changed in the range of 0 to 0.05, stress-stimulated luminescence was confirmed in the near infrared region (>750 nm).

[0167] [21. Whether or not mechanoluminescence occurs when co-doped ions are alkali metal ions other than Li] Next, we investigated whether mechanoluminescence occurs when the co-doped ions are alkali metal ions other than Li, such as Na, K, Rb, or Cs ions. In particular, we investigated the presence or absence of mechanoluminescence when the co-doped ions are 0.6 mol% Nd ions as the luminescent center ion and 0.2 mol% Na, K, Rb, or Cs ions as the co-doped ions.

[0168] As a result, as shown in FIG. 27, stress-stimulated luminescence was confirmed in the near infrared region (>750 nm) regardless of whether the co-doped ions were Na ions, K ions, Rb ions, or Cs ions.

[0169] [22. Whether or not mechanoluminescence occurs when other element ions are added together with Nd ions as the luminescence center ions] Next, we investigated whether mechanoluminescence occurs when multiple luminescence center ions are present. In particular, in this study, as a representative example, we confirmed the presence or absence of mechanoluminescence in the case where the co-doped ion is 10 mol% Li ion, the first luminescence center ion is 0.4 mol% Nd ion, and the second luminescence center ion is 0.4 mol% of any one of ions selected from Cr (chromium), Mn (manganese), Cu (copper), Ag (silver), Ce (cerium), Pr (praseodymium), Sm (samarium), Eu (europium), Tb (terbium), and Yb (ytterbium).

[0170] As a result, as shown in Fig. 28, regardless of the second luminescence center ion, mechanoluminescence was confirmed in the visible region (≦750 nm). In addition, for each of the Mn, Ag, Ce, Pr, Sm, Eu, Tb, and Yb ions, mechanoluminescence was also confirmed in the near-infrared region (>750 nm).

[0171] [23. Whether or not mechanoluminescence occurs when the concentration of Nd, Yb, or Tb ions is changed] Next, for Yb or Tb examined in the above section [22. Presence or absence of mechanoluminescence when other element ions are added together with Nd ions as luminescence center ions], the presence or absence of mechanoluminescence in the near infrared region was confirmed when the concentration of the first luminescence center ion (Nd ion) and the concentration of the second luminescence center ion (Yb ion or Tb ion) were changed.

[0172] In particular, in this study, as a representative example, the case where the co-doped ion is 10 mol% Li ion, the first luminescent center ion is 0.2 mol% Nd ion, and the second luminescent center ion is 0.6 mol% Yb ion was confirmed. In addition, the case where the co-doped ion is 10 mol% Li ion, the first luminescent center ion is 0.6 mol% Nd ion, and the second luminescent center ion is 0.2 mol% Tb ion was also confirmed.

[0173] As a result, as shown in FIG. 29, stress-stimulated luminescence was confirmed even in the near infrared region (>750 nm) regardless of whether the second luminescence center ion was a Yb ion or a Tb ion.

[0174] As described above, according to the stress-stimulated luminescent material of the present invention, alkali metal ions and luminescent center ions are solid-dissolved in ZnO, so that it is possible to provide a stress-stimulated luminescent material using ZnO as a base material.

[0175] Finally, the above-mentioned embodiments are merely examples of the present invention, and the present invention is not limited to the above-mentioned embodiments. Therefore, even if the above-mentioned embodiments are different, various modifications can be made depending on the design, etc., as long as they do not deviate from the technical idea of ​​the present invention.

Claims

1. A method for producing a stress-stimulated luminescent material using ZnO as a base material, comprising mixing a zinc compound, a luminescence center supplying compound which supplies luminescence center ions, and a predetermined co-doped ion supplying compound which supplies co-doped ions, and firing the mixture (excluding a mixture containing a solid protective agent which is melted by heating to isolate a reaction system from an oxidizing atmosphere) in an oxidizing atmosphere, the luminescence center ion is a Nd ion or a Nd ion and an ion of any one element selected from the group consisting of Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb; The co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba; The method for producing a stress-stimulated luminescent material using ZnO as a base material is characterized in that the stress-stimulated luminescent material has a composition represented by the general formula ZnO:E x M y (wherein E is the co-doped ion and M is the luminescent center ion), where x = 0.0001 to 0.7 and y = 0.001 to 0.

2.

2. A method for producing a stress-stimulated luminescent material using ZnO as a base material, comprising the steps of: making an aqueous solution containing zinc ions, in which a luminescent center ion and a predetermined co-doped ion are present, basic, or reacting said aqueous solution with a sulfide, coprecipitating said co-doped ion and luminescent center ion with zinc hydroxide or zinc sulfide, and firing said coprecipitate (excluding those containing a solid protective agent which is melted by heating and isolates a reaction system from an oxidizing atmosphere) in an oxidizing atmosphere, the luminescence center ion is a Nd ion or a Nd ion and an ion of any one element selected from the group consisting of Cr, Mn, Cu, Ag, Ce, Pr, Sm, Eu, Tb, and Yb; The co-doped ion is an ion of any one element selected from Li, Na, K, Rb, and Cs, or an ion of Li and Ba; The method for producing a stress-stimulated luminescent material using ZnO as a base material is characterized in that the stress-stimulated luminescent material has a composition represented by the general formula ZnO:E x M y (wherein E is the co-doped ion and M is the luminescent center ion), where x = 0.0001 to 0.7 and y = 0.001 to 0.2.

Citation Information

Patent Citations

  • Self-activating light-emitting material capable of responding to multiple stimulations such as light stimulation, heat stimulation and force stimulation

    CN107488448A

  • Reaction method for molten medium protection, and preparation method of stress luminescent fluorescent powder

    CN112143488A

  • Inorganic thin film emitting light by force and manufacture thereof

    JP1999120801A

  • High luminance stress light-emission material, its preparation and light-emitting method using the same material

    JP2001049251A

  • Process for producing zinc sulfide particle

    JP2005053735A